Perancangan Web Sistem Pembelian, Persediaan dan Penjualan Kantin Sekolah Al-Husna Berbasis Web dan Database Menggunakan Metode User Centered Design - Muhammad Subhana (bit-Tech, 2024)
The Al-Husna School canteen provides food and other supplies that are ready to assist and serve students and teachers according to their needs. The school canteen members consist of seven people who provide food and other items to ensure that the needs of students and teachers are met. Sometimes, there are members who are not registered as official canteen members, and this can be considered illegal as they provide food without the knowledge of the canteen manager. Each canteen member is only allowed to supply their food once in the canteen for sale. If their stock runs out, they are not allowed to restock their food so that the remaining food from other members' supplies can also be sold out. The issue with this situation is that not only are there members who are not registered as canteen members and are unfair in providing food stock in the school canteen, but also errors in the canteen's records, such as input mistakes, forgetting to record canteen activities, and errors in the canteen's financial reports. Therefore, there is a need to develop a web-based program using PHP and MySQL programming languages. The method used for evaluating this website is the User-Centered Design method, which includes several indicators for providing feedback. Using this method, there is one sample or user, the canteen manager, who evaluates the website based on the User-Centered Design indicators. The results from data processing with a direct calculation show a score of 370, indicating that the system is feasible.